2017
DOI: 10.18203/2349-2902.isj20175484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autologous platelet-rich plasma in the promotion of healing of chronic ulcers

Abstract: Background: Chronic ulcers are a big health problem worldwide. Having a great impact at personal, social and professional levels. The use of autologous Platelet Rich Plasma (PRP) is a major advance in the treatment of these ulcers as an easy and cost-effective method. Platelets provide numerous growth factors enhancing tissue healing. The aim of this study was to evaluate the safety and efficacy of autologous platelet-rich plasma as a treatment of chronic non-healing ulcers.Methods: Autologous PRP was prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Likewise, Tendas et al reported improvement in ulcers following PRP application to pressure ulcers nine times during 4 months . Raslan et al applied PRP to chronic wounds in 24 patients, including pressure ulcers, and reported a significant improvement . In a study conducted by Kakudo et al it was seen that there is a complete healing in the chronic ulcers including pressure ulcers after dressing with PRP gel.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Tendas et al reported improvement in ulcers following PRP application to pressure ulcers nine times during 4 months . Raslan et al applied PRP to chronic wounds in 24 patients, including pressure ulcers, and reported a significant improvement . In a study conducted by Kakudo et al it was seen that there is a complete healing in the chronic ulcers including pressure ulcers after dressing with PRP gel.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous plateletderived wound-healing factors have been proposed to regulate wound healing of chronic cutaneous ulcers by promoting the formation of granulation tissue in the early healing phase. Researchers reported the usefulness of PRP in the treatment of chronic ulcers including pressure ulcer [12][13][14][15][16][17][18]. However, further studies have been suggested for consolidation of these findings [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported the usefulness of PRP in the treatment of chronic ulcers including pressure ulcer [12][13][14][15][16][17][18]. However, further studies have been suggested for consolidation of these findings [12,[16][17][18]. Also, most of the previous studies assessed the effect of PRP on two-dimensional characteristics, assessing the area of the ulcer and clinical improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that PRP acts as an effective therapy for muscle injury, chronic wounds, and atrophic and contractile scars by rejuvenating skin tissue and texture (Nita et al, 2013;A Hamid et al, 2014;Raslan et al, 2017). However, other studies have shown no statistically significant difference between PRP and control groups regarding wound healing (Buchwald et al, 2008;Martinez-Zapata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%